Evaluation of toll-like receptor 4 expression in human bone marrow mesenchymal stem cells by lipopolysaccharides from Shigella. (September 2018) - Hashemzadeh, Mohammad Reza; Eslaminejad, Mohamadreza Baghaban; Salman Yazdi, Reza; Aflatoonian, Reza
Abstract: Lipopolysaccharides (LPS) from gram negative bacteria stimulate toll-like receptor 4 (TLR4) expression in immune cells. Recent reports state that bone marrow-derived cells such as mesenchymal stem cells (MSCs) also express TLR proteins. Numerous researches have studied the effect of a number of LPSs on TLR4 expression, but no data exists on the effect of LPSs from different strains of one bacterial genus on TLR4 expression. In this study, we investigate the effects of various concentrations of LPS from different Shigella strains on TLR4 expression in human bone marrow (hBM)-MSCs. At the mRNA level, we have found that untreated hBM-MSCs (control) did not express TLR4 compared to the experimental groups. Cells treated with LPS from Shigella flexneri had the highest expression of TLR4, whereas cells treated with LPS from Shigella sonnei had the lowest expression. We observed that LPSs had a dose-dependent effect on TLR4 expression in all of the treatment groups. ELISA findings for interleukin-6 secretion have confirmed mRNA expression results for all treatment groups. Hence, LPS from S. flexneri can be considered as an optimum LPS to stimulate the immune system for vaccine production against shigellosis. Also, TLR activation in hBM-MSCs can modulate their function such as homing.